Gerechtigkeit als Methodenfrage Mit Kommentaren von Carsten Bäcker und Michael Potacs - Reimer, Franz (Mohr Siebeck, 2020)
Is justice an argument in the close-meshed contemporary legal order? Or does justice only apply to the extent the legislator wants to accomplish through its norms? Franz Reimer shows that even in strictest adherence to the law, justice is an omnipresent and indisputable question of methodology.
PublicationDate: 20200710
Keywords: Rechtsanwendung -- Rechtstheorie -- Juristische Methodenlehre -- Rechtsextremismus -- freiheitliche demokratische Grundordnung -- Rechtsgefühl -- positives Recht -- Allgemeines -- Rechtsphilosophie